Analysis of Factors Affecting Cash Waqf Collection in Indonesia: Analytic Network Process-Delphi Approach - Alifia (SMART Insight, 2021)
Cash waqf is one of the instruments that is quite effective for the socio-economic development of the country, creates a new job market and helps the poor. However, in practice cash waqf has not been fully utilized by the government. There are several gaps and problems that need to be resolved to improve the performance of waqf in Indonesia. Therefore, the author tries to analyze what factors affect the collection of cash waqf. The method that the author uses is the Analytic Network Process (ANP) by collecting existing problems and solutions that can be offered. The analysis of this data processing shows the main problems, namely regulations, institutions and externals. The solution cluster also provides the same solution as the problem, namely; regulatory, institutional and external.